Content analysis of reported activities of the United Nations Road Safety Collaboration Members during the Decade of Action for Road Safety 2011–2020 - Sean Alan Flannigan; Meleckidzedeck Khayesi (BMJ Open)
Objective Several activities were planned for the Decade of Action (DOA) for Road Safety 2011–2020, covering key policies and interventions on road safety. Knowledge of the activities implemented by key actors is currently lacking in the literature. This study answers the question: what activities were implemented during the DOA by the United Nations Road Safety Collaboration (UNRSC) members?Design The study used content analysis techniques to extract and analyse information from five United Nations Secretary General’s reports, which summarise the activities reported by UNRSC members.Setting The primary setting for this study are 116 countries in which activities supporting the DOA were conducted.Outcome measures Frequency of themes and subthemes that emerged from reported activities are identified and cross-tabulated by year of report, country level of income, geographical region and organisation type.Results Over the entire DOA, establishment of institutions and lead agencies as well as the development of national strategies featured prominently under the theme of management. This theme was steadily reported across regions, country income level and organisation type. Workshops, training and major events regarding road safety increased in frequency of reporting throughout the decade as did developing and promoting the basic road and vehicle systems supportive of road safety. It is further noted that other key activities like infrastructure and behaviour change that are required for a balanced approach to road safety policy were also attended to by various organisations. Activities related to road safety enforcement and post-crash response as well as activities in low-income countries appeared to be less reported.Conclusion The wide range of activities reported by UNRSC members over the entire DOA need to be sustained and evaluated in years to come if they are to have a significant impact on reducing road traffic deaths and injuries at national and international levels.